LINGUISTIC EXPRESSION WITH REFERRENCE TO SEMIOTIC IN ULOS OF WEDDING CEREMONY OF BATAK TOBA - Hendro Doglas Simamora (LINGUISTICA, 2018)
This study was deal with linguistic expression, in semiotics of ulos in wedding ceremony of bataktoba. This research used qualitative method which concerned with developing explanations of experience or on data. The source of the data was taken from the ulosin wedding ceremony of batak toba, and relevant with the transcript of interviewing by three informants with some criterias, that is the most dominant population in three different surename in Tarutung, at the age of 45 to 55 years old and have the recognition from each surename. The instruments that is used in this study was tape recorder, camera, and also the book which relevant to the data. In technique of analyzing data, descriptive qualitative data analysis stage is identifying the ornament, reducing the ornament which are not relevant, classifying, interpreting, analyzing and concluding the findings. There are three kinds of ulos used in wedding ceremony of BatakToba, they are ulosragidup, ulosragihotang, and ulossadum. Each ulos have topisokkar which explain that everything in this world have the limit and the color depend to the ceremony that is performed. In ulosragidup, there are hatirsymbolized of wealth, sigumang symbolized the hope of the giver of this ulos for the receiver to works right and efficient also, batuniansimun symbolizing the health, sisikniikansymbolizing a good life, tidy life, even in a crowded of life, and alsojungkit symbolizing in having an organized life well. In ulosragihotangthere are unok-unok, symbolized be a wise person like the humus,andjungkit. In ulossadum, there is torna where this symbol to remind the people that Batak people come from mountain.Keywords: Semiotic, Ulos in Wedding Ceremony of BatakToba, Ornaments.